Peran Komunikas Keluarga Dalam Pembangunan Karakter Anak Usia Remaja - Yehezkiel Situmorang; Merline Mesti Kukus (Peneliti.net, 2022)
This study aims to determine the role of communication in the development of children's character in their teens. This is done because many teenagers have bad characters, are rude, and like to curse. For this reason, parental warfare is very necessary. This study uses a descriptive qualitative research method where the data collected and presented is in the form of words. There are also obstacles experienced by parents in building communication with children, namely, parents who are too busy with work, children who are stubborn and difficult to manage, too broad association. For this reason, parents must be more proactive in controlling and teaching their children repeatedly. There are several things that parents must do in educating their children, namely teaching children to do good habits, mutual respect and respect for fellow family members.